(untitled) (Journal on studies and research of academic knowledge, 2022)
Yerba mate, (Ilex paraguariensis A. St. Hil.) is a plant native to sub-tropical South America which is used for the preparation of various stimulating drinks, and drinks and is part of the traditions of the region. This plant also has several beneficial health properties and serves as raw material for the cosmetic, nutraceutical, and pharmaceutical industries. The consumption of yerba mate, a very popular drink in South America, is spreading widely throughout the world due to its positive effects on health. It is also used in the preparation of ice cream mixes, sweets, confectionery products, among others. In the Paraguayan market, there are many brands of both processed and compound yerba mate; however, there is no public data about forms of consumption and consumer preferences. For these reasons, a survey was made about the consumption habits and preferences in relation to industrialized yerba mate using two electronic forms. With the data obtained, a descriptive statistics analysis was performed through. It was observed that the subjects preferred compound yerba mate and that they make their choice based on taste. Tereré is the most popular form of yerba consumption, which increases in the summer; and this is independent of the subjects’ occupations and academic background.